Copper‐Catalyzed Tandem CC/CO Bond‐Forming Reactions of ortho‐Halo‐β‐chlorostyrenes with Ketones: Synthesis of 4‐Trifluoromethylbenzoxepines. Issue 2 (16th January 2013) - Sun, Lei‐Lei; Hu, Bo‐Lun; Tang, Ri‐Yuan; Deng, Chen‐Liang; Zhang, Xing‐Guo
Abstract A copper‐catalyzed cyclization reaction of trifluoromethyl‐containing ortho‐halo‐β‐chlorostyrenes with ketones has been developed. Using a combination of copper(I) bromide, 2, 2, 6, 6‐tetramethylheptane‐3, 5‐dione and sodium tert‐butoxide, a variety of 4‐trifluoromethylbenzoxepines was prepared in moderate to good yields by the tandem α‐alkenylation of ketones with subsequent O‐arylation.